Evaluation of Acute Oral Toxicity of a Polyherbal Ayurvedic Formulation in Wistar Rats as per OECD 423 - Sourabh Giri Baballi Umeshgiri; Apoorva Nagraj; Radhika Hollehonnuru Meghraj; A.K. Srinivasamurthy (International Journal of Ayurveda and Pharma Research, 2025)
The present study systematically evaluated the acute oral toxicity profile of Amrith Noni Artho Plus - a polyherbal Ayurvedic formulation containing Morinda citrifolia (Noni), Vitex negundo (Nirgundi), Boswellia serrata (Shallaki), and Commiphora wightii (Guggulu) - in accordance with OECD Guideline 423. Twelve female Wistar rats were subjected to a stepwise testing protocol involving initial (Step 1) and confirmatory (Step 2) phases, with three animals per dose group receiving single oral administrations of either 300mg/kg or 2000mg/kg body weight (limit test dose) via gavage. The formulation was suspended in normal saline (10ml/kg) and administered following overnight fasting. Animals underwent intensive clinical monitoring at predefined intervals (10 min, 30 min, 1h, 2h, 4h, 6h) post-dosing followed by twice-daily observations for 14 days. No mortality or treatment-related clinical signs of toxicity (including behavioural alterations, neurological symptoms, or autonomic disturbances) were observed at any dose level. Body weight trajectories and food/water consumption patterns remained normal throughout the study period, with no statistically significant deviations from baseline (p > 0.05). Gross pathological examination upon termination revealed no abnormalities in vital organs (liver, kidneys, heart, and spleen), and organ-to-body weight ratios fell within normal physiological ranges. The absence of adverse effects at 2000mg/kg classifies this formulation as Category 5 ("unclassified") under the OECD Globally Harmonized System, indicating an exceptionally wide safety margin. This study demonstrates that Amrith Noni Artho Plus is safe at doses up to 2000mg/kg, supporting its non-toxic nature and potential for safe therapeutic use.